Is percutaneous proximal gracilis tenotomy as effective and safe as the open procedure?. (December 2015) - Hachache, Bilal; Eid, Tony; Ghosn, Elias; Sebaaly, Amer; Kharrat, Khalil; Ghanem, Ismat
Purpose: There is currently an increasing trend for percutaneous surgical interventions mainly in children with cerebral palsy (CP). The purpose of this study was to evaluate the effectiveness and safety of percutaneous proximal gracilis tenotomy (PPGT) in children with CP scheduled for hip adductor tenotomy. Methods: This is a prospective study of 59 hips in 31 consecutive patients with CP scheduled for hip adductor tenotomy in the setting of multilevel tenotomies or hip osteotomy (femoral or Dega). A pediatric orthopedic surgeon conducted a percutaneous adductor longus and gracilis tenotomy through the same stab wound. Another surgeon extended the wound to explore what had been cut during the PPGT, and completed the tenotomy if necessary (open proximal gracilis tenotomy; OPGT). Hip abduction with the hip and knee extended (HA) was assessed by a third surgeon (1) immediately before PPGT, i.e., directly after percutaneous adductor longus tenotomy (prePPGT), (2) after PPGT (postPPGT), and (3) following OPGT (postOPGT), using a goniometer, in a standardized reproducible manner. All three surgeons were blinded to each other's findings. Primary end-points included the percentage of muscle portion sectioned percutaneously and the improvement of HA angle. Comparison between HA before and after PPGT was performed using a paired t test with 95 % confidence interval (CI), and comparison between HA after PPGT and OPGT was performed using a Student's t -test with 95 % CI. The bleeding was assessed and other iatrogenic lesions were identified. The relationship between HA after PPGT and the percentage of muscle portion sectioned percutaneously was evaluated by calculating the Pearson correlation coefficient ( p < 0.01). Results: Mean HA measured 33.71 degrees prePPGT and increased to 45.90 degrees postPPGT ( p < 0.0001). The postOPGT HA averaged 48.71 degrees with no statistically significant gain compared with postPPGT ( p = 0.21). The muscular portion of gracilis origin was cut to an average of 91.95 %; completely in only 14 hips, between 90 and 100 % in 35 hips, between 70 and 90 % in 9 hips, and between 60 and 70 % in 1 hip. The gain in HA did not correlate with the extent of the muscular portion sectioned percutaneously ( R = −0.043). Minimal accidental section of adductor brevis postPPGT was encountered in 39 hips. Considerable bleeding postPPGT with hematoma formation requiring hemostasis during the open control procedure occurred in 30 hips. Partial iatrogenic injury of the anterior branch of the obturator nerve was encountered in one patient bilaterally with severe adductor contracture, due to an anatomic too medial variant. Conclusions: This is the only prospective study concerning the outcome of PPGT. Although PPGT is fast, simple and effective, it is not as safe as the open procedure even when performed correctly by an experienced surgeon, mainly because of the increased risk of bleeding. The findings of the current study do not support its use as a 'standard-of-care' technique in children with hip adductor contracture. Level of evidence: Level II therapeutic study—prospective comparative study.